Laparoscopic Cholecystectomy in Moynihan's Hump, Varices of Paracholedochal Plexuses With Superficial Course of Inferior Vena Cava at Calot's Triangle: Case Report - Imtiaz Wani (Clinical Case Reports)
ABSTRACT Anatomical variations of the vascular supply of the hepatobiliary system are rare to see. A sound knowledge of congenital variations of vascular patterns in and around Calot's triangle is essential for the safe practice of laparoscopic cholecystectomy. A case of 34‐year‐old female is reported who has intraoperative diagnosis of Moynihan's hump, varices of paracholedochal plexuses, superficially placed portal vein in anterior plane with superficial course of inferior vena cava at Calot's triangle during laparoscopic cholecystectomy. An uneventful laparoscopic cholecystectomy was done with utmost meticulous approach and careful surgical dissection in Calot's triangle to avoid any inadvertent injury to anomalous vasculature. An occurrence of congenital anomaly of Moynihan's hump, varices of paracholedochal plexuses, superficially placed portal vein in anterior plane with superficial course of inferior vena cava at Calot's triangle is extremely rare and incidentally diagnosed intraoperatively. This case report is the first kind of case of world reporting occurrence of a multiple vascular anomalies diagnosed during laparoscopic cholecystectomy. Culture of safe practice of laparoscopic cholecystectomy is to be advocated and this is to be called as “Srinagar Cholecystectomy”.